2020
DOI: 10.1111/ans.16023
|View full text |Cite
|
Sign up to set email alerts
|

Non‐operative management of small post‐appendicectomy intra‐abdominal abscess is safe and effective

Abstract: Background: Intra-abdominal abscess (IAA) post-appendicectomy occurs in 1.4-4.4% of cases. Non-operative management of small (<4 cm) post-appendicectomy IAA in children is well established, but minimal evidence exists in adults. Percutaneous catheter drainage is considered standard treatment for IAA, yet outcome data for post-appendicectomy IAA are sparse. The aims of this study were to assess the effectiveness of non-operative management of small (<4 cm diameter) IAA and the outcomes of percutaneous drainage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The treatment of PAA smaller than 3 cm is less subject of debate in children. Although historically, especially in adults, invasive treatment procedures for PAA were preferred, several more recent studies have reported promising results of non-operative treatment of small PAA with treatment successes ranging between 84 and 100% ( 6 , 12 , 18 – 20 ). This is in line with the results of our multicenter cohort, in which all patients with PAA smaller than 3 cm were successfully treated with a non-invasive treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of PAA smaller than 3 cm is less subject of debate in children. Although historically, especially in adults, invasive treatment procedures for PAA were preferred, several more recent studies have reported promising results of non-operative treatment of small PAA with treatment successes ranging between 84 and 100% ( 6 , 12 , 18 – 20 ). This is in line with the results of our multicenter cohort, in which all patients with PAA smaller than 3 cm were successfully treated with a non-invasive treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…It is more common in acute and chronic inflammation, stones and tumors in the internal organs of the abdominal cavity, as well as perforation and rupture of the digestive tract. [2,3] Periappendiceal abscess caused by conservative treatment of chronic appendicitis and appendectomy is not uncommon in clinically practice, but the cases of abdominal wall abscesses following appendectomy are relatively rare, and it is even rarer in the third trimester. From January 1980 to September 2021, Pubmed searched the literature published and there were no reports of “pregnancy” and “periumbilical abscess.”…”
Section: Discussionmentioning
confidence: 99%
“…Combining medical therapy with invasive procedures is required as IV antibiotics generally do not reach effective concentrations within abscess cavities except in small immature abscesses [ 2 , 38 ]. Abscesses measuring 1–4 cm in diameter may occasionally resolve themselves by means of antibiotic treatment alone and, thus, warrant a wait-and-see approach [ 2 , 17 , 39 ]. A more aggressive approach should be based on the clinical course of disease.…”
Section: Treatmentmentioning
confidence: 99%